Process Optimization of Biosorption Hg(II), Cu(II) and Ni(II) Ions onto Dead Anaerobic Biomass using a Two-Level Full Factorial Design and Response Surface Methodology, Batch Systems - Ridha, Mohanad Jasim Mohammed (Nahrain University College of Engineering Journal, 2017)
Dead anaerobic biomass prepared from drying bed wastewater treatment plant were used as adsorbents for the biosorption studies of mercury, copper and nickel ions from synthetic wastewater. The main and interactive effects on uptake of Hg(II), Cu(II) and Ni(II) in this study are investigated through the model equations designed by a two-level full factorial design. Experiments designed by central composite design were carried out and the process response was modeled. Heavy metals removal efficiency and uptake have sequence order Hg(II) > Cu(II) > Ni(II) under tested conditions, Hg(II) offers the strongest component that able to displace Cu(II) and Ni(II) from their sites, while Ni(II) ions was the weakest adsorbed component. Best removal efficiencies were 96.2, 90.3 and 82.4 when temperature 400C, pH 6, initial metal ion concentration 10 mg/l, biomass loading 6 g/l, contact time 180 min, and 200 rpm for Hg(II), Cu(II) and Ni(II) respectively.The results predicted using factorial regression model showed high values of regression coefficients (R2) 0.945 indicating good agreement with experimental data. The main biosorption mechanisms were complexation and physical adsorption onto natural active functional groups. It is observed that biosorption of these metals was a surface process.